Measuring the perceived container leasing prices in liner shipping network design with empty container repositioning. (October 2016) - Zheng, Jianfeng; Sun, Zhuo; Zhang, Fangjun
Highlights: Measure the perceived container leasing prices helpful for decision making on container leasing strategies. Propose a practical liner shipping network design problem with empty container repositioning. Present a two-stage optimization method. Abstract: This paper aims to measure the perceived container leasing prices at different ports by presenting a two-stage optimization method. In stage I, we propose a practical liner shipping network design problem with empty container repositioning. The proposed problem further considers the use of foldable containers and allows the mutual substitution between empty containers to decrease the number of empty containers to be repositioned. In stage II, the inverse optimization technique is used to determine the perceived container leasing prices at different ports, based on the solution obtained in stage I. Based on a set of candidate liner shipping service routes, a mixed-integer nonlinear programming model is built for the proposed problem in stage I. The nonlinear terms are linearized by introducing the auxiliary variables. Numerical experiments based on a realistic Asia-Europe-Oceania liner shipping network are carried out to account for the effectiveness of our two-stage optimization method.